(untitled) (Journal of the College of Basic Education, 2022)
Importance of research how to take advantage of the effect of overlap and the merger between the designs scheduling exercise in learning some offensive skills hand reel. The problem of the research centered on the lack of attention to trainers specialized schools using the style of overlap and the merger between the methods of learning schedule. So the researcher considered to provide an educational curriculum on the proposal in accordance with the overlap between the exercise Ashoaia- variable in learning some offensive skills hand reel. .The objective of this research to prepare a curriculum based on the overlap between the exercise Ashoaia- variable for some offensive skills hand reel, and identify the impact of the curriculum in learning offensive skills hand reel, either the research hypotheses were: There are significant differences between the results of the tribal tests and a posteriori the research group and in favor of the post tests in some offensive skills hand reel. The research methodology as the researcher using the experimental method for suitability to the nature of the search. The research sample (10) players from the National Center for the care of sports talent handball. As it proceeded researcher curriculum education (Part president, Applied activity) using the overlap and the merger between the indiscriminate exercise - variable .walve is prepared by the researcher and rely on the opinions of experts and specialists in the application of these exercises and all selected skills as promised researcher educational exercises a private manner Ashoaia_ variable for the group to search it is a overlap and the merger between the two modes of who shall player to learn and perform more than skill in module per different Petkrarat in terms of distance and time, and the angle and shape of the skill itself and these exercises included three skills of a correction, handling, receipt and clapotement, and the application of the curriculum under the direct supervision by the researcher. The researcher found to: 1.dharorh adoption scheduling interoperability exercise (random - variable). 2.etbin that the overlap between the stylistic exercise-random variable has a significant and positive effect on the eye testers in all the skills that have been studied. 3.etbin that skill correction better than the rest of the studied skills that have achieved the highest percentage in the posttest results The researcher recommends: - Use method to schedule exercise interoperability (random - variable) to learn the skills reel hand for juniors. 2.alakhz the results of this study and adoption in learning the skills hand reel.